Review Article on Ashmari w.s.r. to Urolithiasis - Kumar, Rajendra; Kumar, Ashok; Singh, Narinder; Kumar, P Hemantha (International Research Journal of Ayurveda & Yoga, 2021)
Urolithiasis or Renal Stone Disease, described as Ashmari in Ayurveda is the third most common disease condition of urinary tract, after Urinary Tract Infection (UTI) and Benign Prostatic Hyperplasia (BPH). In spite of recent technological advances in the management of the urolithiasis, prevention of recurrence of diseases still remains a very significant challenge. In this review article, an attempt was made to compile the all aspects of urolithiasis from aetiology to management principles. Moreover to this attempt, this review also summarized to recent advancement in the clinical management of disease. The review tried to find out the gaps in the management and prevention of the disease. The review found an enormous need to allocate substantial resources for research & development for filling these gaps. The review found lack of resource allocation in finding the preventive solution for the disease. Moreover lack of focus on preventing the recurrence after surgical clearance. Ayurveda proposes surgery for management of Ashmari with large size stone while emphasising on various drugs for management of newly diagnosed case. Ayurveda may be helpful in not only management but also prevention as it stresses upon the role of diet, lifestyle and medicine for the prevention of the disease.